Effectiveness of using polymers and cement for soil stabilization - Verma, Neeraj (My University, 2013)
The aim of the study was to determine the value of Unconfined compressive strength and CBR values of Soil after stabilizing it with Cement and Polymer. Soil stabilization has been widely used as an alternative to substitute the lack of suitable material on site. The use of nontraditional chemical stabilizers in soil improvement is growing daily. In this study a laboratory experiment was conducted to evaluate the effects of waterborne polymer on unconfined compression strength on sandy soil and CBR Test on clayey soil .The laboratory tests were performed including grain size of sandy soil, unit weight, and unconfined compressive strength test. The sand and various amounts of polymer (2%, 3%, and 4%) and cement (20%, 30%, and 40%) were mixed with all of them into dough using hand mixing in laboratory conditions. The samples were subjected to unconfined compression tests to determine their strength after 7 days of curing. The results of the tests indicated that the waterborne polymer significantly improved the unconfined compression strength of sandy soils which have susceptibility of liquefaction. Polymer modified the engineering properties of soil through physical bonding. The amount of polymer required to modify the engineering properties was directly related to specific surface and soil particle coating thickness. Polymer amended soils displayed a reduced performance compared to cement amended soils.
Master of Engineering-Structural
Keywords: Soil; Stabilisation; Polymers; Cement